Alumina‐Supported Alkali and Alkaline Earth Metal‐Based Catalyst for Selective Decarboxylation of Itaconic Acid to Methacrylic Acid. Issue 14 (10th April 2021) - Ali, Hadi; Kansal, Sushil Kumar; Saravanamurugan, Shunmugavel
Abstract: The present study focuses on selective decarboxylation of itaconic acid (IA) to methacrylic acid (MAA) using alkali and alkaline earth metals (Na, K, Mg and Ca) supported on Al2 O3, prepared by incipient wet impregnation approach. The parent Al2 O3, predominantly composed of the boehmite phase, is entirely transformed to γ‐Al2 O3 phase upon impregnating calcium, based on XRD analysis, and this is not the case for other metals employed in this study. FTIR analysis corroborates the complete decomposition of nitrate precursor in the case of calcium than other metals (Na, K and Mg). UV‐Vis analysis using diffused reflectance mode suggests that Ca incorporated on to the Al2 O3 matrix. Among the catalysts employed, the highest yield of methacrylic acid (MAA) (46.7 %) is achieved with 5 wt % Ca/Al2 O3 at 250 °C, 20 bar N2 after 3 h. Moreover, 15.1 % of α‐hydroxyisobutyric acid (α‐HIBA), a hydrated product of MAA, is also obtained, and thus, the combined yield of MAA and α‐HIBA is 61.8 %. The selective decarboxylation of IA to MAA/α‐HIBA can be correlated with the number of basic sites present in the 5 wt % Ca/Al2 O3, which possess the highest number of basic sites than other catalysts. Abstract : Decarboxylation of itaconic acid to methacrylic acid (46.7 %) and its hydrated product α‐hydroxybutyric acid (15.2 %) is achieved in good yield with calcium incorporated on Al2 O3 in water in the absence of an external base. In contrast, other alkaline and alkaline earth metal incorporated on Al2 O3 employed in this study display inferior catalytic activity.